Breaking the surface an art/archaeology of prehistoric architecture - Bailey, Douglass W. (Douglass Whitfield) 1963- (Oxford University Press, 2018)
Breaking the Surface will be a disruption to traditional archaeological approaches to the prehistoric past. Having performed fieldwork on the early Neolithic pit-houses of southeastern Europe for over 20 years, the author aims to confront a major development in human history--digging, or the creation of holes. The book begins with a detailed examination of the extant remains of Neolithic pit-houses, the roofed dugout structures that are the earliest evidence for settled habitation in Europe. Rather than seek confirmation for what has already been theorized about their use (e.g., housing, storage, refuse), the author turns to the more specific actions of the people who dug these holes in the surface, and, more critically, to the consequences that those prehistoric actions had on those people's understanding of their place(s) in their ground worlds: how digging into the surface altered their perspectives of themselves and others, and of their world and of other worlds beyond the material and visible. The book turns to how scholars in other disciplines, such as philosophy and linguistic anthropology, have been asking similar questions about holes and the consequences of breaking and cutting. The resulting book offers comprehensive discussions of the philosophy of holes and perforations (particularly the paradox of a hole - does it exist, is it beyond materiality?), the linguistic anthropology of cut- and break-words (what diversity exists in the ways that extant communities talk and think about perforations and perforating), and the perceptual psychology of concavities (the case that holes attract our visual attentions)"-- |c Provided by publisher.